2014
DOI: 10.1080/10401334.2013.857329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bedside Physical Diagnosis Training on Third-Year Medical Students' Physical Exam Skills

Abstract: Bedside physical diagnosis rounds appear to have elevated the overall OSCE score for 3rd-year medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Different types of structured skills training programs have been developed leading to different outcomes with respect to students’ performance regarding physical examination skills or suturing. A structured bedside training where attendings received guidelines to demonstrate and observe students doing physical examinations, led to better student performance in half of the OSCE stations covering heart and lung examination [44], while another study with specific weekly bedside instructions in physical examination skills compared with the usual bedside teaching showed better OSCE results for musculoskeletal, pulmonary and gastrointestinal but not for cardiovascular exam [50]. …”
Section: Resultsmentioning
confidence: 99%
“…Different types of structured skills training programs have been developed leading to different outcomes with respect to students’ performance regarding physical examination skills or suturing. A structured bedside training where attendings received guidelines to demonstrate and observe students doing physical examinations, led to better student performance in half of the OSCE stations covering heart and lung examination [44], while another study with specific weekly bedside instructions in physical examination skills compared with the usual bedside teaching showed better OSCE results for musculoskeletal, pulmonary and gastrointestinal but not for cardiovascular exam [50]. …”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25] Compared to our review of the 2013 literature relevant to general medicine educators, 26 we found more multi-institutional studies of high quality. Similar to last year, resident continuity clinic and handoffs were areas of focus.…”
Section: Discussionmentioning
confidence: 98%
“…However, the results of our qualitative analysis are congruent with previous studies that have shown the effectiveness of live modeling experiences on acquiring procedural (including physical examination) and cognitive skills. 8,9 There were a few challenges that we identified to the incorporation of a scheduled modeling experience for neurology clerks, and the biggest difficulty was how to work the experience around clinic no-shows. There were several limitations to this study as well.…”
Section: Flow and Organization Of Examinationmentioning
confidence: 99%
“…6,7 Modeling of clinical encounters has been shown to improve both physical examination and procedural skills, and can be effective for teaching humanism and professionalism values. [8][9][10] The aim of this study was to evaluate whether a scheduled modeling experience for third-year medical students starting their neurology clerkship increased overall student exposure to clinical skills modeling during the clerkship. In addition, we intended to discover using qualitative thematic analysis what specific learning points were acquired during the experience.…”
mentioning
confidence: 99%